SUNTEL pilot study: first school-based integration of the ugly duckling sign and a dedicated e-learning platform with peer education for melanoma prevention - Stanganelli, Ignazio; Magi, Serena; Costa, Elisabetta; Medri, Matelda; Gentilini, Franca; Scutellà, Chiara; De Zerbi, Daniela; Ravaglia, Giorgia; Gerosa, Silvia; Zamagni, Federica; Doccioli, Chiara; Gandini, Sara; et al. (Frontiers in Oncology, 2025)
IntroductionEducational initiatives among young people are pivotal in promoting healthy behaviors, yet only a few studies to date have used peer education in schools to convey health messages for melanoma prevention. Here we report the results of a peer-education-based skin cancer prevention program combined with teledidactics (SUN Education and TELematic Learning – SUNTEL) targeting high school students in Italy.MethodsIn 2023-2024, thirty third-year high school students attended training sessions to become peer educators and then conducted interventions across first-year students using a multimedia platform. Students targeted by the peer-education intervention completed pre- and post-intervention questionnaires to assess changes in their knowledge, attitudes and behaviours regarding melanoma prevention. Marginal homogeneity tests were used to compare responses in the pre- vs. post-intervention questionnaires.ResultsThe study population included 323 students (56.7% boys) mostly aged 14–16 years. Most participants had fair/light dark skin (>97%); 24% had freckles, and over one third developed skin rash often/always after UV exposure. Students’ knowledge about melanoma risk factors and prevention, and attitude about UV exposure, changed significantly after the intervention, e.g., students wanting to use a tanning bed/lamp dropped from 9.6% to 3.8% (p-value <0.001), and those aware that using a tanning bed/lamp is as risky as tanning in the sun rose from 75.4% to 90.5% (p-value <0.001). Knowledge of the ABCDE rule rose from 7.5% to 96.6%; for the ugly duckling sign, the change was from 9.1% to 91.2%.Conclusionse-learning/web-based tools and peer-education proved highly effective in enhancing students’ knowledge regarding melanoma prevention and recognition, proving comparably or even more effective compared to teachers-/physicians-led educational approaches. Notably, this is the first school-based program to introduce the “ugly duckling” sign, a simple and reproducible rule for early melanoma detection. Sustained message reinforcement and parental involvement will be key to achieving lasting behavioral change in sun safety.